2017
DOI: 10.15171/ijhpm.2017.123
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Researchers and Policy-Makers Collaboration in Evidence-Informed Policy-Making in Nigeria: Outcome of a Two-Way Secondment Model between University and Health Ministry

Abstract: Background: There is need to strengthen institutions and mechanisms that can more systematically promote interactions between researchers, policy-makers and other stakeholders who can influence the uptake of research findings. In this article, we report the outcome of a two-way secondment model between Ebonyi State University (EBSU) and Ebonyi State Ministry of Health (ESMoH) in Nigeria as an innovative collaborative strategy to promote capacity enhancement for evidence-to-policy-to-action. Methods: This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 26 publications
0
36
0
Order By: Relevance
“…This collective brokering model would have been hampered in less affluent or more turbulent climates, without the time afforded by ring-fenced funding from solvent, stable organisations. Previous senior inter-organisational relationships created mutually receptive environments, which other studies have also found important (Uneke et al, 2017, Cheetham et al, 2018. Allies, champions and chaperones formed a multi-level network at all levels within host organisations, without which KM team members struggled to find direction or make progress.…”
Section: Summary Of Findingsmentioning
confidence: 95%
“…This collective brokering model would have been hampered in less affluent or more turbulent climates, without the time afforded by ring-fenced funding from solvent, stable organisations. Previous senior inter-organisational relationships created mutually receptive environments, which other studies have also found important (Uneke et al, 2017, Cheetham et al, 2018. Allies, champions and chaperones formed a multi-level network at all levels within host organisations, without which KM team members struggled to find direction or make progress.…”
Section: Summary Of Findingsmentioning
confidence: 95%
“…One approach is improving the partnership and dialogue between PHC researchers, policymakers, providers and other interest groups to produce and apply the new knowledge needed. Another important action is to develop new pathways and communities of researchers needed to prioritise and produce the knowledge needed 11…”
Section: Introductionmentioning
confidence: 99%
“…Lectures and interactive discussions were held around the following topics: 1) Introduction to health policy and systems research/building evidence-informed policy environments; (2) Capacity development and enhancement for evidence-informed health policy-making; (3) Acquisition, assessment, adaptation & application of evidence in health policy-making and (4) Building effective linkage, partnership & exchange between health policy-makers and researchers in Nigeria. Participants in the workshop were also broken up into six focus groups to discuss the topic ‘Bridging the gap between health policy-makers & researchers’Uneke et al (2018) [34]Nigeria10 researchers and 10 senior policy staffPart-time secondment, up to 2 working days per week over a period of 6 monthsTwo-way secondment (policy-makers working in research teams and researchers working within government health programs)Researchers seconded to policy teams provided research expertise to several projects, including the State Malaria Elimination program, reproductive health services, and primary healthcareResearch secondees were instructed to (1) build trust and understand policy-maker’s evidence needs; (2) play an expert advisory role and provide scientific evidence to guide on policy issues; and (3) provide capacity enhancement for policy-makersPolicy-maker experiences (in research organisations) were also reported; however, this is out of scope for the present reviewUltimately, the two-way secondment aimed to increase collaboration between policy-makers and researchers in Nigeria and build capacity for ongoing evidence-informed policy-makingFollowing the secondments, all participants (both researchers and policy-makers) attended a policy dialogue event where they received training on preparing a policy brief; the event was used to produce national guidelines on malaria control using insecticide-treated nets in Ebonyi StateUneke et al (2018) [35]Nigeria45 participants: researchers from the Implementation Research Team, policy-makers (from the Ministry of Health, Local Government Area, state primary healthcare development agency) and representatives from non-governmental organisations3 daysTraining course (face-to-face)The aim of the training program was to increase the capacity of policy-makers and researchers to undertake KT and promote evidence-based policy; the 3-day training workshop included 15 modules (5 per day)The 15 modules wereIntroduction to health policy and health systems; Introduction to KT (IKT and End-of-Grant KT); Research priority setting; Leadership capacity development and managing political interference; Getting research into policy and practice; KT models measures; Research evidence in health policy-making and health policy implementation; Health policy advocacy, demand creation, consensus-building and negotiations; KT tools and strategies for stakeholders and end users engagement; Policy formulation and implementation process. Modules were taught each day by way of lectures and group work sessions; lecture sessions used learning tools such as PowerPoint slides and handouts; group work consisted of focus group discussion, question/answer sessions and group workPapers emerging from the KTSI run by the Canadian Institutes of Health ResearchKho et al (2009) [36]CanadaPrimarily doctoral students or PhDs (early career researchers)4 daysTraining course (face-to-face)The aims of the KTSI in relation to health services, p...…”
Section: Resultsmentioning
confidence: 99%
“…Participants in the Canadian Summer Institute, from which three papers emerged [3638], were all researchers or graduate students interested in KT research. The duration of the training initiatives varied from part time secondments, which lasted between 6 months [34] and up to 2 years [30], to Santacroce et al’s [32] program, which was embedded into existing training programs for nurse scientists over several years (pre- and post-doctoral coursework). The other programs [31, 33, 35, 36] were brief (between 1 and 4 days) face-to-face courses or were delivered during a single session [37, 38].…”
Section: Resultsmentioning
confidence: 99%